LAW NUMBER 17 OF 2022 CONCERNING WEST SUMATRA PROVINCE IN THE FIQH SIYASAH DUSTURIYAH PERSPECTIVE - Kamil, Roky Insan; Maghfira, Saadatul; Pertiwi, Dian; Nofrianti, Mami (JISRAH: Jurnal Integrasi Ilmu Syariah, 2024)
This research aims to find legal provisions regarding Mentawai cultural discrimination in Law no. 17 of 2022 concerning West Sumatra Province, what is the siyasah fiqh perspective regarding Mentawai cultural discrimination in Law Number 17 of 2022 concerning West Sumatra Province. The aim of this research is to find out and explain the legal provisions regarding Mentawai cultural discrimination in Law Number 17 of 2022 concerning West Sumatra Province. The author can conclude several things as follows: The impact of the policy of Law Number 17 of 2022 concerning the Province of West Sumatra, on Mentawai ethnicity is considered to be less suitable, the government is considered to be ignoring the Mentawai tribe, this can be seen from the fact that Mentawai is not an area with the Minangkabau tribe.